Acinic Cell Carcinoma of Minor Salivary Gland of the Base of Tongue That Required Reconstructive Surgery - Kota Wada; Subaru Watanabe; Yuji Ando; Yoichi Seino; Hiroshi Moriyama (Case Reports in Otolaryngology)
Acinic cell carcinoma of minor salivary gland of the base of tongue is very rare. Squamous cell carcinoma is the most common tumor in the base of tongue. We present a patient with gigantic acinic cell carcinoma of the base of tongue. This patient required emergency tracheotomy before surgery, because he had dyspnea when he came to our hospital. We removed this tumor by pull-through method and performed reconstructive surgery using a rectus abdominis myocutaneous flap. It was a case that to preserved movement of the tongue and swallowing function by keeping lingual arteries and hypoglossal nerves. This case was an extremely rare case of ACC of the base of tongue that required reconstructive surgery.